2023
DOI: 10.31234/osf.io/xeuty
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soundscapes of morality: Linking music preferences and moral values through lyrics and audio

Abstract: Music is a fundamental element in every culture, serving as a universal means of expressing our emotions, feelings, and beliefs. This work investigates the link between our moral values and musical choices through lyrics and audio analyses. We align the psychometric scores of 1,480 participants to acoustics and lyrics features obtained from the top 5 songs of their preferred music artists from Facebook Page Likes. We employ a variety of lyric text processing techniques, including lexicon-based approaches and B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 89 publications
(115 reference statements)
0
0
0
Order By: Relevance
“…According to the moral prediction results in recent studies, foundations related to Care and Fairness were challenging to predict [18,66]. Our results again showed that moral values related to Care and Fairness are more complex to predict than values related to Authority, Purity, and Loyalty.…”
Section: Plos Onesupporting
confidence: 67%
See 4 more Smart Citations
“…According to the moral prediction results in recent studies, foundations related to Care and Fairness were challenging to predict [18,66]. Our results again showed that moral values related to Care and Fairness are more complex to predict than values related to Authority, Purity, and Loyalty.…”
Section: Plos Onesupporting
confidence: 67%
“…People who value more Individualising values preferred artists whose songs' lyrics talk about joy, anticipation and trust. Those concerned more about ingroup and Binding values liked artists whose songs contained more romantic topics and disliked lyrics that implied negative emotions such as sadness, fear, or disgust [18]. However, as in the previous studies [55,66], the Individualising foundations remained challenging to predict.…”
Section: Links Between Moral Values and Musical Tastesmentioning
confidence: 84%
See 3 more Smart Citations